The utility of diagnostic tests for immune‐mediated hemolytic anemia. (9th September 2019) - ; MacNeill, Amy L.; Dandrieux, Julien; Lubas, George; Seelig, Davis; Szladovits, Balázs
Abstract: Background: A definitive diagnosis of immune‐mediated hemolytic anemia (IMHA) can be difficult to make. However, it is critical to differentiate IMHA from other causes of anemia due to the impact on prognosis and outcome for IMHA patients. Recently published American College of Veterinary Internal Medicine recommendations for the diagnosis of IMHA should be followed to concurrently confirm ongoing anemia, verify in vivo hemolysis, and detect anti‐erythrocyte antibodies. The reliability of immunologic IMHA tests varies depending on which test is used and how it is performed. Objectives: Our aims were to determine which tests are currently used in veterinary medicine to diagnose IMHA and review the utility of assays that have historically been used to diagnose IMHA. Methods: A short survey was designed to see which diagnostic tests for IMHA were currently being used by veterinary practices. The survey was distributed via list‐serves to veterinarians and veterinary technologists. A literature review was performed to report the utility of diagnostic tests for the diagnosis of IMHA. Results: Survey respondents indicated a variability in test protocols used to diagnose IMHA. Most respondents perform saline agglutination or Coombs' tests to detect anti‐erythrocyte antibodies. Additional tests that can be used to support a diagnosis of IMHA are discussed in this review. Conclusions: A standardized diagnostic approach should be followed to differentiate IMHA from other causes of anemia. Test methodology can vary from one laboratory to another, and clinicians should be familiar with the procedures used by their laboratory.